Development of Interactive Multimedia Based on Learning Cycle 5E in IPAS Learning for Fourth Grade Elementary School - -Afni, Laila Nur; Suntari , Yustia; Putra , Adi; Afni, Laila Nur (JURNAL PENDIDIKAN DASAR NUSANTARA, 2024)
This research aims to develop interactive multimedia based on the 5E learning cycle called MIKBI in science and social learning for grade IV elementary schools. The method in this research uses R&D by adapting the ADDIE development model with stages, namely: 1) Analysis, 2) Design, 3) Development, 4) Implementation, and 5) Evaluation.. The research was carried out at SDN Tanjung Barat 07 with 28 test subjects. Product validity is measured through the assessment of material experts obtained an average score of 92.00% with very decent criteria, media experts gain value 91.76% with very feasible criteria, and linguists gain marks 92.00% with very feasible criteria.Product validity results shows an average value of 91.92% with very feasible criteria. Product testing is carried out in 3 stages, namely one-to-one evaluationan average score of 85.13% with a very decent category, small group evaluation obtained a score of 85.85% in the very feasible category, and the field test evaluation trial obtained a score of 87.08% in the very feasible category so that the average feasibility percentage score obtained at the student trial stage was 86.02% with very feasible criteria. The results of the research show that MIKBI is very suitable for use as science learning media for Indonesian Cultural Wealth material for class IV elementary schools.